Building communities over time: The case of collectivities and churches of two neighbourhoods in Lisbon - Marat-Mendes, T.; Anastácio, M. (The architecture of need: Collective-use facilities and community service in the twentieth century’ international conference: Book of Abstracts, 2024)
This presentation focus in the analysis of specific urban facilities, object of our study, the collectivities and churches of the neighborhoods Encarnação and Caselas, in Lisbon, built under the affordable housing Program Casas Económicas promoted by Estado Novo, in the 1950s.